U.S - Japan strategic alliances in the semiconductor industry : (Pacific Reseach Center Stanford University, 1992)
This book reviews the evolution of strategic alliances involving U.S. and Japanese companies in the semiconductor industry and analyzes whether alliances can contribute to the renewal of an industry faced with stiff competition from Japan. It includes case studies, alternative future scenarios, and suggestions for government and industry